Quantitative assessment of the blood-brain barrier opening caused by Streptococcus agalactiae hyaluronidase in a BALB/c mouse model. Issue 1 (December 2017) - Luo, Su; Cao, Qing; Ma, Ke; Wang, Zhaofei; Liu, Guangjin; Lu, Chengping; Liu, Yongjie
Abstract Streptococcus agalactiae is a pathogen causing meningitis in animals and humans. However, little is known about the entry ofS. agalactiae into brain tissue. In this study, we developed a BALB/c mouse model based on the intravenous injection of β-galactosidase-positiveEscherichia coli M5 as an indicator of blood-brain barrier (BBB) opening. Under physiological conditions, the BBB is impermeable toE. coli M5. In pathological conditions caused byS. agalactiae, E. coli M5 is capable of penetrating the brain through a disrupted BBB. The level of BBB opening can be assessed by quantitative measurement ofE. coli M5 loads per gram of brain tissue. Further, we used the model to evaluate the role ofS. agalactiae hyaluronidase in BBB opening. The inactivation ofhylB gene encoding a hyaluronidase, HylB, resulted in significantly decreasedE. coli M5 colonization, and the intravenous injection of purified HylB protein induced BBB opening in a dose-dependent manner. This finding verified the direct role of HylB in BBB invasion and traversal, and further demonstrated the practicability of thein vivo mouse model established in this study. This model will help to understand theS. agalactiae –host interactions that are involved in this bacterial traversal of the BBB and to develop efficacious strategies to prevent central nervous system infections.